Level of dietary diversity score and its predictors among children aged 6–23 months: a linear mixed model analysis of the 2019 Ethiopian Mini Demographic Health Survey - Kusse Urmale Mare; Getahun Fentaw Mulaw; Osman Ahmed Mohammed (BMJ Public Health)
Background The dietary diversity score (DDS) of children is one of the indicators as part of infant and young child feeding practices. This study aimed to assess the level of DDS and its determinants among Ethiopian children aged 6–23 months.Methods This study analysed retrospective cross-sectional data on a weighted sample of 1511 children aged 6–23 months after extracting it from the Ethiopian Mini Demographic and Health Survey 2019. A a linear mixed model was fitted and expressed as adjusted beta coefficients with a 95% CI. Finally, predictors with a p value <0.05 were considered statistically significant. Measures of variation were explained by intraclass correlation coefficients (ICC), and model fitness was determined using the Akaike information criterion.Result The mean (±SD) DDS of children was 2.8 (±1.5). Only 56.3%, 13.4% and 11.6% of children met the minimum meal frequency (MMF), minimum dietary diversity score and minimum acceptable diet, respectively. The full model ICC was 0.266, which implied that 26.6% of the total variance of DDS among children was attributed to the differences between clusters. For a 1-month increase in the child’s age, the DDS of children will increase by 0.016 units, holding all other variables constant. Also, for every 1-year increase in maternal education, a 0.057-unit increase in the DDS of children is predicted. Children from wealthy families, having mothers who have had media exposure, meeting MMF and taking fewer than 30 min to reach a nearby water supply have been proven to increase the DDS.Conclusion In Ethiopia, the DDS of children is very low. To improve DDS enhancing maternal literacy, revenue production activities, media exposure and access to water sources should be prioritised. The significance of feeding children regularly throughout the day should be emphasised.